2013
DOI: 10.1590/s1984-29612013005000010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cryptosporidiumspecies and genotypes in dairy cattle in Brazil

Abstract: In this study, we identified Cryptosporidium species and genotypes present in dairy cattle in the central region of São Paulo state, Brazil. Fecal specimens were collected from 200 animals (100 calves and 100 cows) in ten dairy farms. Fecal samples were examined using microscopic examination (ME), enzyme immunoassay (EIA) and polymerase chain reaction (PCR). Cryptosporidium species and genotypes were determined by restriction fragment length polymorphism (RFLP) or DNA sequencing analysis of the SSU-rRNA and GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
(83 reference statements)
3
15
0
1
Order By: Relevance
“…bovis , in line with other reports [36,61,64,65,66], but many researchers have detected these species more often when compared to C . parvum among cattle older than 2 months [44,53,59,66]. In others studies was suggested that infection with C .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…bovis , in line with other reports [36,61,64,65,66], but many researchers have detected these species more often when compared to C . parvum among cattle older than 2 months [44,53,59,66]. In others studies was suggested that infection with C .…”
Section: Discussionsupporting
confidence: 91%
“…This species is mainly identified among heifers and adult animals [44,63,69], but some investigators in Brazil identified C . andersoni at a high frequency in young calves too [66,70]. In our study, the prevalence of C .…”
Section: Discussionmentioning
confidence: 68%
“…Nested PCR amplification was performed using the set of primers previously described for detection of Cryptosporidium spp. [36,37], G. duodenalis [38,39], and L. intracellularis DNA [8,40], with some modifications. Nested PCR products from the genera Cryptosporidium and Giardia with the expected sizes were analyzed by automated direct sequencing using a 3500 Genetic Analyzer (Applied Biosystems, Foster City, CA) and BigDye6 Terminator v3.1 Cycle Sequencing Kit.…”
Section: Lawsonia Intracellularis Cryptosporidium Parvum Andmentioning
confidence: 99%
“…106 Thus far, relative to the large number of studies in industrial-107 ized nations, only a few have been conducted to examine the dis-108 tribution of Cryptosporidium species in dairy cattle in developing 109 countries, where animals are managed very differently (Amer 110 et al, 2010;Inpankaew et al, 2010;Khan et al, 2010;Imre et al, 111 2011;Meireles et al, 2011;Muhid et al, 2011;wang et al, 112 2011a,b;Kang'ethe et al, 2012;Venu et al, 2012;Silva et al, 113 2013;Zhang et al, 2013). Most of these studies have shown a 114 common occurrence of C. bovis, C. ryanae, and C. andersoni in 115 pre-weaned calves, in addition to C. parvum Q3 (Meireles et al, 116 2011;Muhid et al, 2011;Wang et al, 2011a,b;Venu et al, 2012; 117 Silva et al, 2013;Zhang et al, 2013). A small number of these stud- approximately 830-bp fragment of the small subunit (SSU) rRNA 168 gene as previously described (Feng et al, 2007).…”
mentioning
confidence: 99%